A GUI Based Teaching And Learning Software For System Sizing Of A Stand-Alone Hybrid Solar Electricity System - Sulaiman, Marizan; Mohamad Nor, Ahmad Fateh; Omar, Rosli (BRIS Journal Of Advanced Science & Technology (BRISJAST), 2015)
-